Two new species and a new record of Comesomatidae (Nematoda, Araeolaimida) from the Southern Ocean - Sujing Fu; Jianfeng Mou; Kun Liu; Shuyi Zhang; Heshan Lin (ZooKeys, 2025)
Two new marine nematode species of the genus Sabatieria and a new record of Hopperia beaglense Chen & Vincx, 1998 belonging to the family Comesomatidae are described from the Southern Ocean using morphological and molecular data. Sabatieria cosmonautae sp. nov. is characterized by body length 1786–2230 μm, short cephalic setae, lateral differentiation of body cuticle with sparse punctations starting from amphid to near tail tip, spiral amphidial fovea with three turns, spicules arcuate and 1.2–1.5 cloacal body diameters long, with straight dorso-caudal gubernacular apophyses, and 16 or 17 precloacal supplements. Sabatieria crassilonga sp. nov. is characterized by body length 2628–3613 μm, short cephalic setae, cuticle with lateral differentiation of coarser and irregularly spaced punctations extending from anterior edge of amphid to the tail region, amphidial fovea spiral with 2.5 turns, males with spicules 1.2–1.5 cloacal body diameters long, gubernaculum with a long straight dorso-caudal apophysis, and 20 or 21 fine precloacal supplements. Hopperia beaglense, which was originally described from the Strait of Magellan and the Beagle Channel, is recorded from the Southern Ocean for the first time. Phylogenetic analysis based on concatenated 18S + 28S rRNA sequences places the two new species and the new record within Comesomatidae. The tree topology shows Comesomatidae forming a well-supported monophyletic clade, whereas the genus Sabatieria is not monophyletic.